2020
DOI: 10.1016/j.neurobiolaging.2020.05.013
|View full text |Cite
|
Sign up to set email alerts
|

5XFAD mice show early-onset gap encoding deficits in the auditory cortex

Abstract: Early detection will be crucial for effective treatment or prevention of Alzheimer's disease. The identification and validation of early, non-invasive biomarkers is therefore key to avoiding the most devastating aspects of Alzheimer's. Measures of central auditory processing such as gap detection have recently emerged as potential biomarkers in both human patients and the 5XFAD mouse model of Alzheimer's. Full validation of gap detection deficits as a biomarker will require detailed understanding of the underl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…The significant reduction was found in ABR peaks IV and V, which are generated by neural activities of inferior colliculus, nuclei of lateral lemniscus, and medial geniculate body in the upper brainstem. It was also reported that the 5xFAD mice have early onset of deficits in auditory gap detection at 2 months old (Kaylegian et al, 2019;Weible et al, 2020). These data demonstrated that dysfunctions of hearing could occur much earlier than the typical AD phenotypes occurring.…”
Section: Figmentioning
confidence: 60%
See 4 more Smart Citations
“…The significant reduction was found in ABR peaks IV and V, which are generated by neural activities of inferior colliculus, nuclei of lateral lemniscus, and medial geniculate body in the upper brainstem. It was also reported that the 5xFAD mice have early onset of deficits in auditory gap detection at 2 months old (Kaylegian et al, 2019;Weible et al, 2020). These data demonstrated that dysfunctions of hearing could occur much earlier than the typical AD phenotypes occurring.…”
Section: Figmentioning
confidence: 60%
“…The significant reduction of ABR peaks IV and V (which are generated by neural activities of inferior colliculus, nuclei of lateral lemniscus, and medial geniculate body in the upper brainstem) in the APP/PS1 AD mice could be found at 3 months old (Liu et al, 2020). It was also reported that the 5xFAD mice have early onset of deficits in auditory gap detection, which could be detectable at about 2 months old and became progressive worse afterwards (Kaylegian et al, 2019; Weible et al, 2020). These data demonstrated that dysfunctions of hearing occurred much earlier than the appearance of typical AD phenotypes, such as spatial learning deficit, in APP/PS1 AD mice by 6-7 months of age (Reiserer et al, 2007; Ordonez-Gutierrez et al, 2015, 2016).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations